Distinct leukocyte populations and cytokine secretion profiles define tumoral and peritumoral areas in renal cell carcinoma - Borcinova, Martina; Bartolini, Robin; Foley, Lily Koumbas; Novak, Vojtech; Taborska, Pavla; Stakheev, Dmitry; Rataj, Michal; Smrz, Daniel; Fialova, Martina; Hacek, Jaromir; Komarc, Martin; Vesely, Stepan; et al. (Translational oncology, 2024)
Renal cell carcinoma (RCC) is a common malignancy frequently diagnosed at the metastatic stage. We performed a comprehensive analysis of the tumor immune microenvironment (TIME) in RCC patients, including the peritumoral tissue microenvironment, to characterize the phenotypic patterns and functional characteristics of infiltrating immune cells. T cells from various compartments (peripheral blood, tumor, peritumoral area, and adjacent healthy renal tissue) were assessed using flow cytometry and Luminex analyses, both before and after T cell-specific stimulation, to evaluate activation status and migratory potential. Our findings demonstrated that tumor-infiltrating lymphocytes (TILs) exhibited heightened cytokine production compared to peritumoral T cells (pTILs), acting as the primary source of cytotoxic markers (IFN-γ, granzyme B, and FasL). CD8+ T cells primarily employed Fas Ligand for cytotoxicity, while CD4+ T cells relied on CD107a. In addition, a statistically significant negative correlation between patient mortality and the presence of CD4+CD107+ pTILs was demonstrated. The engagement with the PD-1/PD-L1 pathway was also more evident in CD4+ and CD8+ pTILs as opposed to TILs. PD-L1 expression in the non-leukocyte fraction of the tumor tissue was relatively lower than in their leukocytic counterparts and upon stimulation, peripheral blood T cells displayed much stronger responses to stimulation than TILs and pTILs. Our results suggest that tumor and peritumoral T cells exhibit limited responsiveness to additional activation signals, while peripheral T cells retain their capacity to respond to stimulatory signals.